The role of multimedia tools in teaching foreign languages - Cherednichenko, Galina; Shapran, Ludmila; Kunytsia, Lyudmila (My University, 2012)
In the article the authors define the importance of research about the impact of multimedia and CALL on language acquisition within limited curriculum hours, possibility to combine self-study with classroom training, to provide systematic feedback, regular progress checking, dynamic language improvement.
Keywords: англійська мова; мультимедія; комп’ютеризація навчання; multimedia; foreign language; CALL; ESP; кафедра ділової іноземної мови та міжнародної комунікації